2020
DOI: 10.47119/ijrp100571720201346
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dynamic Contrast Enhancement MR Imaging as A Modality to Differentiate between Benign and Malignant bone lesion

Abstract: The study was aimed to determine Time Intensity Curve (TIC) type and slope value on Dynamic Contrast Enhancement Magnetic Resonance Imaging (DCE-MRI) examination technique to differentiate between benign and malignant bone lesion. The study was done on December 2018 to July 2019 with retrospective cross sectional analytic study. The samples were bone lesion patients which was examined with Dynamic Contrast Enhancement on 3T MRI. The sample size were 15 subjects, consisted of 8 (53.3%) males and 7 (46.7%) femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
(19 reference statements)
1
4
0
Order By: Relevance
“…The highest quantitative of TIC results using %slope and ME representation covered its steepest slope value which accurately reflected tumor vascularization. These results were similar to previous studies conducted by Varidha and Setiawati in 2020, they reported that the mean slope of osteosarcoma was 68.59%/s 26 . Yong Park et al (2014) stated that the steepest slope and early relative elevation signal intensity have a potential role in differentiating benign and malignant soft tissue tumor 27 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The highest quantitative of TIC results using %slope and ME representation covered its steepest slope value which accurately reflected tumor vascularization. These results were similar to previous studies conducted by Varidha and Setiawati in 2020, they reported that the mean slope of osteosarcoma was 68.59%/s 26 . Yong Park et al (2014) stated that the steepest slope and early relative elevation signal intensity have a potential role in differentiating benign and malignant soft tissue tumor 27 .…”
Section: Discussionsupporting
confidence: 93%
“…Tucbilek et al (2004) stated that the steepest lope value accurately reflects tumor vascularization, the malignant soft tissue tumor showed early elevation signal intensity and steepest slope e.g. liposarcoma 28 . Two cases of chondroblastic and osteoblastic OS with the presented of ADC value mapping and TIC on DCE were described on Figure 1 and Figure 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the majority of the CI curves of the VAs exhibited an early peak of enhancement before 200 sec (T-peak <200 sec), with this enhancement peak being weak (CI-peak <2.0), after which the contrast intensity remained constant for a period of 400–600 sec, in what is known as the ‘plateau phase’. Varidha et al ( 33 ) reported that a CI curve of rapid early enhancement followed by a plateau has limited specificity in terms of benign vascular lesion characterization. They also suggested that early enhancement is a result of high microvascularization and tissue perfusion, whereas a plateau phase results from the accumulation of contrast in the neovasculature and its surrounding interstitium due to a change in endothelial permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Varidha et al (33) reported that a CI curve of rapid early enhancement followed by a plateau has limited specificity in terms of benign vascular lesion characterization. They also suggested that early enhancement is a result of high microvascularization and tissue perfusion, whereas a plateau phase results from the accumulation of contrast in the neovasculature and its surrounding interstitium due to a change in endothelial permeability.…”
Section: ------------------------------------------------------------...mentioning
confidence: 99%